Groundbreakers: Human Remains and Radiocarbon Dates from the First Burials in Churchyards on Gotland - Klevnäs, Alison; Ljung, Cecilia; Noterman, Astrid; Brownlee, Emma (Current Swedish Archaeology, 2025)
This paper presents osteological analyses and radiocarbon dates from human remains found in early churchyards on the Baltic island of Gotland. Graves from the first phases of burial have been discovered beside churches on Gotland on many occasions since the late nineteenth century, usually during preparations for new interments. Previous work has focused on the artefacts found with many of them, which suggest that the early churchyard dead were buried in costume closely resembling that worn in the last phases of the traditional grave fields. These finds have been a key source for research into the chronology and process of the Christianization of Gotland during the late Viking Age and early medieval period. Neglected, however, are the human remains which were sometimes recovered alongside the artefacts, but until now escaped research attention. Here we present analyses of the remains of 26 individuals recovered from Garda churchyard, with smaller numbers from Stånga, Havdhem and Fardhem. The results contribute osteological characterization of the early adopters of churchyard burial, along with new absolute dates for the establishment and use of the new Christian burial sites, and demonstrate that the practice of furnished burial was maintained in churchyards for an extended period.